Answer:
[tex](p^{9} -25)[/tex]
[tex](g^{2} -36)[/tex]
Step-by-step explanation:
Verify each case
case A) we have
[tex](p^{9} -25)[/tex]
we know that
[tex]p^{9}=(p^{3})^{2}[/tex]
[tex]25=(5)^{2}[/tex]
[tex](p^{9} -25)=(p^{3})^{2}-(5)^{2}[/tex] -----> is a difference of two squares
case B) we have
[tex](a^{8} -18)[/tex]
we know that
[tex]a^{8}[/tex] -----> is not a perfect square
[tex]18[/tex] -----> is not a perfect square
therefore
[tex](a^{8} -18)[/tex] -----> is not a difference of two squares
case C) we have
[tex](g^{2} -36)[/tex]
we know that
[tex]g^{2}=(g)^{2}[/tex]
[tex]36=(6)^{2}[/tex]
[tex](g^{2} -36)=(g)^{2}-(6)^{2}[/tex] -----> is a difference of two squares